Local recurrence in head and neck cancer: relationship to radiation resistance and signal transduction. - Gupta, A; Mckenna, W; Weber, C; Feldman, MD; Goldsmith, J; Mick, R; Machtay, M; Rosenthal, D; Bakanauskas, V; Cerniglia, G; Bernhard, E; Weber, R; et al. (2002)
PURPOSE: Locoregional recurrence is the dominant form of treatment failure in head and neck (HandN) cancer. The epidermal growth factor receptor (EGFR) is frequently amplified in this disease (